Transformation of the Restaurant Business as a Result of the COVID-19 Pandemic: Improving the Security of Service and Maintaining the Health of Human Capital - Oleksandr Matsenko; Oleksandra Kubatko; Volodymyr Bardachenko; Kateryna Demchuk (Health Economics and Management Review)
The study identified socio-economic problems in the restaurant business, analyzed the dynamics of its decline and recovery during the pandemic COVID-19, considered innovative trends in the transformation of restaurant management. Systematization of literature sources and approaches to the study of the impact of epidemics and pandemics on restaurant activities showed that until 2019, cases of infection of restaurant visitors occurred. However, they were isolated or local (regional) in nature and attracted the attention of most medical researchers. The COVID-19 pandemic is global in heart and has affected all economic areas, including the restaurant industry. Therefore, the number of scientific papers in this field is proliferating. The urgency of solving the scientific problem is that during the COVID-19 pandemic, restaurant customers' behavior and a significant increase in the number of online orders. This encourages restaurants to respond and transform their business models, business strategies and diversify sales channels. The research method is based on the statistical analysis of restaurant business performance indicators at the global level and the level of Ukraine and the analysis of innovative modern trends in the transformation of the restaurant business. The study results showed that the restaurant industry's main problems in the period of quarantine restrictions and lockdowns are mass layoffs, declining sales, inability to adapt and transform to the new conditions of the restaurant business. Accordingly, the directions of transformation of the restaurant business based on breakthrough innovations to increase customer service safety during the pandemic are proposed. The article focuses on the possibilities of restaurants to promote the health of human capital by diversifying the menu for vulnerable groups, such as children, people with chronic diseases, members of certain racial and ethnic minorities, the elderly. The results of this study can help build a policy in the restaurant industry to overcome the crisis in this area and improve public health. Also, the results can be used by restaurants to increase their competitiveness based on specific transformation measures.